2015
DOI: 10.3892/or.2015.4283
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to endoplasmic reticulum stress mediates cisplatin resistance in human ovarian cancer cells by maintaining endoplasmic reticulum and mitochondrial homeostasis

Abstract: The mechanism of cisplatin resistance in ovarian cancer is not fully understood. In the present study, we showed a critical role for endoplasmic reticulum (ER) stress tolerance in mediating cisplatin resistance in human ovarian cancer cells. We found cisplatin to inhibit the proliferation of two ovarian cancer cell lines: cisplatin-sensitive SKOV3 cells and cisplatin‑resistant SKOV3/DDP cells. However, the effect was greater in the cisplatin-sensitive SKOV3 cells. Cisplatin treatment induced ER stress in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…The PTP can further lead to mitochondrial swelling and mitochondrial outer membrane permeabilization (MOMP), with a consequent release of Cyto C and caspase-activating factors and the induction of cell apoptosis (11). In our previous study, using the cytoplasmic Ca 2+ -indicating fluorophore Fluo-4/AM and the mitochondrial Ca 2+ -indicating fluorophore Rhod-2/ AM, we found that cisplatin causes pro-apoptotic Ca 2+ release from the ER to the cytosol and mitochondria, thus leading to cytosolic and mitochondrial Ca 2+ overload, which contributes to ER-mediated apoptosis and mitochondria-mediated apoptosis in cisplatin-sensitive SKOV3 ovarian cancer cells (12). These results have confirmed that a large release of Ca 2+ from the ER to the cytosol and mitochondria is very important for ER-mediated apoptosis and mitochondrial apoptosis.…”
Section: Introductionmentioning
confidence: 92%
“…The PTP can further lead to mitochondrial swelling and mitochondrial outer membrane permeabilization (MOMP), with a consequent release of Cyto C and caspase-activating factors and the induction of cell apoptosis (11). In our previous study, using the cytoplasmic Ca 2+ -indicating fluorophore Fluo-4/AM and the mitochondrial Ca 2+ -indicating fluorophore Rhod-2/ AM, we found that cisplatin causes pro-apoptotic Ca 2+ release from the ER to the cytosol and mitochondria, thus leading to cytosolic and mitochondrial Ca 2+ overload, which contributes to ER-mediated apoptosis and mitochondria-mediated apoptosis in cisplatin-sensitive SKOV3 ovarian cancer cells (12). These results have confirmed that a large release of Ca 2+ from the ER to the cytosol and mitochondria is very important for ER-mediated apoptosis and mitochondrial apoptosis.…”
Section: Introductionmentioning
confidence: 92%
“…It was reported that cisplatin could induce ERS-associated apoptosis in ovarian cancer cells and that ERS tolerance might be involved in cisplatin resistance. 25 In another recent study, negative regulation of the PI3K/AKT/mTOR signaling pathway was shown to mediate apoptosis in BC cells. 12 Therefore, the conclusions from previous studies provide extra evidence further supporting our results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have highlighted that endoplasmic reticulum (ER) stress may cause cisplatin resistance in ovarian carcinoma by inducing autophagy in cancer cells, allowing them to escape apoptosis. 43,44 Findings from this pathway analysis suggest that future studies of the contribution of ER stress in cisplatin sensitivity is needed to improve our understanding of platinum-resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%